Meningkatkan Kesadaran Beragama Melalui Refleksi Diri Dan Jurnal Spiritualitas Pada Siswa MI - Nurul Qomariyah; Nurul Hidayah; H. Nurul Huda (CV Edujavare Publishing, 2025)
Religious awareness is a crucial aspect of character development among students in Madrasah Ibtidaiyah (MI). However, religious understanding is often limited to cognitive aspects and lacks emphasis on reflective and applicative dimensions in daily life. This study aims to analyze the effectiveness of self-reflection and spiritual journaling as learning methods to enhance students' religious awareness in MI. The research employs a qualitative approach, utilizing data collection techniques such as observation, interviews, and student journal analysis. The findings reveal that self-reflection helps students gain a deeper understanding of their religious experiences, while spiritual journaling serves as a tool for documenting the development of religious values and fostering a habit of critical and introspective thinking about daily behaviors. Additionally, the combination of these methods encourages a stronger connection between religious teachings and students' social lives. Therefore, self-reflection and spiritual journaling can be effective strategies for instilling Islamic values in a sustainable manner.